2020
DOI: 10.14202/vetworld.2020.160-164
|View full text |Cite
|
Sign up to set email alerts
|

The influence of duration on pain stress, oxidative stress, and total antioxidant power status in female dogs undergoing ovariohysterectomy

Abstract: Background and Aim: Ovariohysterectomy (OHE) is a common procedure for sterilization of female dogs. However, knowledge of changes in pain stress, oxidative stress, and total antioxidant power status before, during, and after OHE is limited. The objective of this experiment was to study the effect of duration on pain stress, oxidative stress, and total antioxidant power status in female dogs undergoing OHE. Materials and Methods: Seven female dogs were sterilized using the OHE method. Pain scores, hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 13 publications
2
23
0
Order By: Relevance
“…Similar results were reported by Quarterone et al (2017), who compared ovariohysterectomized and ovariectomized dogs and rats regarding postoperative analgesia (Quarterone et al, 2017). Sakundech et al (2020) also concluded that due to the oxidative stress caused by OHE, the ovariohysterectomized dogs should receive some treatment that can protect their bodies from free radicals [2,22].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar results were reported by Quarterone et al (2017), who compared ovariohysterectomized and ovariectomized dogs and rats regarding postoperative analgesia (Quarterone et al, 2017). Sakundech et al (2020) also concluded that due to the oxidative stress caused by OHE, the ovariohysterectomized dogs should receive some treatment that can protect their bodies from free radicals [2,22].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an increase in the oxidative stress biomarkers after OHE [2,23]. Therefore, the researchers should nd a way that minimizes the harmful effects of free radicals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations